2016
DOI: 10.1136/bmj.h5918
|View full text |Cite
|
Sign up to set email alerts
|

Management of psychotropic drugs during pregnancy

Abstract: Psychiatric conditions (including substance misuse disorders) are serious, potentially life threatening illnesses that can be successfully treated by psychotropic drugs, even during pregnancy. Because few rigorously designed prospective studies have examined the safety of these drugs during pregnancy, the default clinical recommendation has been to discontinue them, especially during the first trimester. However, in the past decade, as more evidence has accumulated, it seems that most psychotropic drugs are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 157 publications
(116 reference statements)
0
69
0
11
Order By: Relevance
“…On the other hand, abstaining from treatment puts the mother at risk of a worsened psychiatric condition, with the dangers this involves for the mother and child. Weighing these options against each other, the recommendation has often been to discontinue treatment, especially during the first trimester 1. However, during the past decade more safety data have accumulated suggesting that antipsychotics are relatively safe to use in pregnancy 1, 2, 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, abstaining from treatment puts the mother at risk of a worsened psychiatric condition, with the dangers this involves for the mother and child. Weighing these options against each other, the recommendation has often been to discontinue treatment, especially during the first trimester 1. However, during the past decade more safety data have accumulated suggesting that antipsychotics are relatively safe to use in pregnancy 1, 2, 3.…”
mentioning
confidence: 99%
“…Weighing these options against each other, the recommendation has often been to discontinue treatment, especially during the first trimester 1. However, during the past decade more safety data have accumulated suggesting that antipsychotics are relatively safe to use in pregnancy 1, 2, 3. It has also been demonstrated that discontinuing ongoing maintenance treatment for severe mood and psychotic disorders during pregnancy carries a high risk of disease recurrence 2.…”
mentioning
confidence: 99%
“…Dünya genelinde bu yönde farklı sınıflandırmalar bulunsa da bunların en bilineni Amerikan İlaç ve Gıda İdaresi (Food and Drug Administration-FDA) başlattığı risk sınıflandırma sistemidir. Bu sınıflandırmaya göre risk "A, B, C, D ve X" kategorilerine ("A" en düşük, "X" ise en yüksek) ayrılır (40). Örneğin, NSAİİ'lerin gebelik kategorisi hamileliğin 1. ve 2. trimesterinde "C" iken son trimesterinde "D"dir (41).…”
Section: Gebelik/fötusunclassified
“…Multiple organizations, including the American College of Obstetricians and Gynecologists,3 American Academy of Pediatrics,4 and most recently the US Preventive Services Task Force,5 have all recommended screening for perinatal mood disorders during pregnancy and post partum. Many different treatment options now exist for women who are diagnosed as having perinatal depression, including psychopharmacologic interventions, such as antidepressants and psychotherapeutic treatments 67…”
Section: Introductionmentioning
confidence: 99%